Watering a lemon tree: Heterogeneous risk taking and monetary policy transmission - Dong Beom Choi; Thomas M. Eisenbach; Tanju Yorulmazer (Federal Reserve Bank of New York, 2015)
We build a general equilibrium model with financial frictions that impede the effectiveness of monetary policy in stimulating output. Agents with heterogeneous productivity can increase investment by levering up, but this increases interim liquidity risk. In equilibrium, the more productive agents choose higher leverage, invest more, and take on higher liquidity risk. Therefore, these agents respond less than the agents with lower productivity to monetary policy that reduces the equilibrium interest rate. Overall quality of investment deteriorates, which can generate a negative spiral, dampening the effect of a monetary stimulus: Worse overall quality leads to lower liquidation values, increasing the cost of liquidity risk. This reduces the demand for loanable funds, further decreasing the interest rate, which then leads to further quality deterioration. When this feedback is strong, monetary policy can lose its effectiveness in stimulating aggregate output even if it leads to significant drops in the interest rate.
Keywords: E52; E58; G20; 330; monetary policy transmission; financial frictions; heterogeneous agents; financial intermediaries